2023
DOI: 10.3390/ijms24043585
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Factor 1, a Goldilocks Transcription Factor from Adrenocortical Organogenesis to Malignancy

Abstract: Steroidogenic factor-1 (SF-1, also termed Ad4BP; NR5A1 in the official nomenclature) is a nuclear receptor transcription factor that plays a crucial role in the regulation of adrenal and gonadal development, function and maintenance. In addition to its classical role in regulating the expression of P450 steroid hydroxylases and other steroidogenic genes, involvement in other key processes such as cell survival/proliferation and cytoskeleton dynamics have also been highlighted for SF-1. SF-1 has a restricted pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 123 publications
2
10
0
Order By: Relevance
“…Overexpression of transcription factor SF‐1 is a marker of malignancy in ACC 43 . An increased SF‐1 dosage in the H295R cell line considerably increases their invasive properties in vitro and in vivo 19,21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of transcription factor SF‐1 is a marker of malignancy in ACC 43 . An increased SF‐1 dosage in the H295R cell line considerably increases their invasive properties in vitro and in vivo 19,21 .…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of transcription factor SF-1 is a marker of malignancy in ACC. 43 An increased SF-1 dosage in the H295R cell line considerably increases their invasive properties in vitro and in vivo. 19,21 We have previously shown that FSCN1 knockdown or treatment with the FSCN1 small molecule inhibitor G2 impaired Matrigel invasion of H295R cells triggered by SF-1 overexpression.…”
Section: Inactivation Of Fscn1 Expression or Pharmacological Antagoni...mentioning
confidence: 99%
“…Steroidogenic factor-1 (SF-1) is a member of the nuclear receptor superfamily first identified as a regulator of p450 enzymes, and is now recognised as a global regulator of steroidogenic gene expression. SF-1 has essential roles in adrenogonadal development and differentiation [181]. Multiple factors modulate SF-1 activity, including post-translational modification, ligand binding and gene dosage.…”
Section: Nuclear Ppins and Regulation Of Transcription Factorsmentioning
confidence: 99%
“…This fusion protein drives the expression of genes involved in cell proliferation and survival, leading to the development of Ewing sarcoma [1,2]. DAX1, also known as NR0B1, is a transcriptional regulator that plays a critical role in the development and function of several endocrine glands, including the adrenal gland and the hypothalamus [3]. Recent studies have also implicated DAX1 in the pathogenesis of Ewing sarcoma (ES), a rare type of bone cancer that primarily affects children and young adults.…”
Section: Introductionmentioning
confidence: 99%